Dental fear, communication, and behavioural management problems in children referred for dental problems - MARLEEN ANTOINETTE KLAASSEN, JACOBUS SIMON JOHANNES VEERKAMP, & JOHAN HOOGSTRATEN (IAPD and Blackwell, 2007)
Referral of children to a specialized paediatric dentist or a specialist clinic in paediatric dentistry is increasingly accepted, and the number of children referred is subsequently growing.